A Study of Antimicrobial Usage Pattern in Dogs at Aizawl, Mizoram, India - , J B Rajesh, B Sunil, N Prejit, Payel Kar, H Prasad (Archives of Current Research International, 2025)
Antibiotics, derived from the Greek word for "opposing life," are drugs that kill or inhibit bacterial growth. Antibiotics are used therapeutically, prophylactically, and as growth promoters. Data were acquired using questionnaires focused on demographics, disease conditions, antibiotic use, and related activities. Most dogs (75.2%) were male and between the ages of 1 to 5 years (54.4%). The most common ailments were skin problems (30.4%) and digestive system disorders (32%). Antibiotic use varies by condition: the most commonly prescribed medications for respiratory problems were Doxycycline (45.95%) and Amoxicillin (21.62%). Cardiac problems were treated primarily with amoxicillin (44.44%). Antibiotics used for skin problems were amoxicillin (27.63%) and clindamycin (23.68%). Antibiotic for gastrointestinal problems was metronidazole (60%). In genito-urinary diseases, amoxicillin was the most used drug (42.86%). The most commonly prescribed antibiotic for musculoskeletal problems was amoxicillin (44.44%). The study focused on prevalent diseases and antibiotic usage in the region. The findings were compared to similar research, highlighting the necessity of appropriate antibiotic selection and enhanced antibiotic sensitivity testing.